2016
DOI: 10.21037/jtd.2016.04.68
|View full text |Cite
|
Sign up to set email alerts
|

Co-morbid psychological dysfunction is associated with a higher risk of asthma exacerbations: a systematic review and meta-analysis

Abstract: Background:The longitudinal associations between psychological dysfunction (PD) and asthma exacerbations (AE) have not been adequately addressed. This study aimed to systematically assess the influence of PD on AE, and to determine whether different PD affects AE differentially. P<0.001], presenting as hospitalizations (RR adj =1.22, 95% CI: 1.12-1.34, P<0.001), unscheduled doctor visits (RR =4.26, 95% CI: 2.52-7.19), and emergency department (ED) visits (RR adj =1.06, 95% CI: 1.01-1.10, P=0.009) because of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
33
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 62 publications
3
33
0
2
Order By: Relevance
“…There was a higher prevalence of psychological symptoms in patients with uncontrolled or severe asthma, which is also similar to other studies (18). The mechanisms that underlie the relationship between psychological symptoms and asthma remain unclear (19). We recently found that anxiety symptoms are associated with greater perceived dyspnea intensity in asthma during bronchoconstriction (16); and that depression and high stress were associated with reduced bronchodilator response (20,21), and altered pattern of inflammation (22), which could be involved in therapy resistance.…”
Section: Discussionsupporting
confidence: 79%
“…There was a higher prevalence of psychological symptoms in patients with uncontrolled or severe asthma, which is also similar to other studies (18). The mechanisms that underlie the relationship between psychological symptoms and asthma remain unclear (19). We recently found that anxiety symptoms are associated with greater perceived dyspnea intensity in asthma during bronchoconstriction (16); and that depression and high stress were associated with reduced bronchodilator response (20,21), and altered pattern of inflammation (22), which could be involved in therapy resistance.…”
Section: Discussionsupporting
confidence: 79%
“…The study showed that adult patients with asthma and comorbid GAD and/or MDD who were titrated to target doses of antidepressants had reduced risk of severe asthma exacerbations and a lower number of asthma‐related outcomes over 1‐ and 2‐year follow‐up periods compared with those who were not optimized to achieve target doses. Although the relationship between asthma and anxiety/depression is well established, to our knowledge, this study is the first to investigate whether antidepressant target dose optimization compared with not achieving antidepressant target doses will improve markers of asthma control 2–4,7–10 …”
Section: Discussionmentioning
confidence: 99%
“…Several proposed mechanisms have explained how mismanaged anxiety and depression may lead to poor asthma outcomes. At the psychological level, stress imparted by anxiety and depression was shown to decrease patients’ sense of self‐worth, perceived self‐efficacy in disease management, and medication adherence, potentially resulting in greater asthma‐related morbidity 3,32–34 . At the physiologic level, psychologic stress may also exacerbate atopic disorders through immune dysregulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations